A Case of Masson’s Tumor of the Penis Presenting as Chronic Pelvic Pain Syndrome - Yanev, Krasimir; Krastanov, Aleksander; Georgiev, Marincho; Tonev, Andrian; Timev, Alexander; Elenkov, Angel (Urology Journal, 2018)
The intravascular papillary endothelial hyperplasia (IPEH) or Masson’s tumor is an unusual and rare benign disease. It is histologically characterized by papillary and anastomosing channel-like structures lined by proliferating e n dothelium. Radiologically, it is usually presented as a heterogenic solid mass with contrast enhancement, withareas resembling necrosis and thrombosis. These signs can easily be attributed to malignancy. The urogenital tractis extremely rarely affected with only 8 cases described in the kidneys and one of the penis. We present a rare case of IPEH at the base of the penis, visible only on MRI, causing chronic pelvic pain and erectile dysfunction. According to available English literature our case is the first in this pelvic location and only the second to affect the penis. Radical excision of the formation cured the condition.